THE DIFFERENCE OF NEUTROPHIL LYMPHOCYTE RATIO (NLR) IN CONVENTIONAL AND ELECTRIC SMOKERS - Sarah, Diah Ayu Siti; Naftali, Zulfikar; Yusmawan, Willy; Suprihati, Suprihati (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Smoking is an unhealthy lifestyle causing health problems that may lead to high morbidity and mortality rates. One way to stop smoking habit is by replacing conventional cigarettes with electric cigarettes. Cigarette smoke exposure can trigger an inflammatory reaction that can be measured using Neutrophil Lymphocyte Ratio (NLR). Aim: Proving of NLR in electric smoker are higher than conventional smoker. Method: The research used descriptive analytic design. The number of samples were 34 people, divided into 17 people each group (conventional smoker and electric smoker). The subjects were asked to fill out a questionnaire and their blood samples were taken by 3 cc. Then, the blood samples were tested in a laboratory to obtain NLR values. The data was then analyzed using unpaired T-test. Result: NLR mean in the conventional smoker group is 1,364 ± 0,28 and 1,791 ± 0,49 in the electric smoker group. The unpaired T-test indicates there is significant difference in the value of NLR between conventional smoker and electric smoker (p=0,005). Conclusion: NLR in electric smoker are higher than conventional smoke.